Keamanan Basis Data Pada Perancangan Sistem Kepakaran Prestasi SMAN Dikota Surakarta - Robi Wariyanto Abdullah; Sri Wulandari; Muqorobin Muqorobin; Fendy Prasetyo Nugroho; Wahyu Wijaya Widiyanto (CCIT (Creative Communication and Innovative Technology) Journal, 2019)
State high schools in Surakarta City have different achievements. To see these achievements, it is necessary to have an expert system that provides information about the achievements of the school to the community, both student achievement and the achievements of teachers or educators. In designing the expertise system of school achievement, it is also necessary to design the database system. Often developers don't pay attention to data security in the database when designing a system. System design is made into the concept of data mapping, Context Diagrams, and Table Relations. This research will also discuss restrictions on database access rights in MySQL which is useful to restrict users from accessing the database. Based on the design, the writer presents a web-based school achievement expertise design system as a means of information on the achievements of public high schools in the city of Surakarta. The method in this study covers literature review, data collection, designing achievement expertise systems, and designing and security procedures for the expert system database at Surakarta Senior High School. The results of this study are the system of school achievement expertise in Surakarta Senior High School based on the categories of achievement, level of achievement, and year of achievement as well as the design database of the school achievement system with regard to database security